WhatIEatInADay: The effects of viewing food diary TikTok videos on young adults’ body image and intent to diet - Drivas, Magdalayna; Reed, Olivia Simone; Berndt-Goke, Maranda (Body image, 2024)
The rise of short-form video content has prompted research into its impact on body image; however, little remains known regarding the effects of exposure to food-related content of this type. The present study aimed to fill this gap in the literature by conducting a between-subjects experiment (N = 316) examining the effects of exposure to low-calorie versus high-calorie “What I Eat in A Day” food diary TikTok videos on young adults’ body appreciation, body dissatisfaction, and diet intentions. Additionally, this study sought to explore how social comparison and mood might affect participants’ responses to these videos. Results indicate that social comparison mediated the relationship between video type (low- vs high- calorie) and positive mood, such that low-calorie videos increased upward social comparison and decreased positive mood, and high-calorie videos increased downward social comparison and increased positive mood. Positive direct effects of positive mood on body appreciation and diet intentions occurred, and a negative direct effect on body dissatisfaction was found. Additionally, positive mood mediated the path from social comparison to diet intentions. These findings highlight the importance of further research into the nuanced impacts of food diary social media content on young adults’ body image and behaviors. •Investigated effects of What I Eat in a Day TikToks on body image and diet intent.•Compared effects of low-calorie vs. high-calorie diet What I Eat in A Day TikToks.•Compared to low-calorie TikToks, high-calorie TikToks led to increased downward social comparison.•Downward social comparison improved body image and increased diet intent.